Comparing medication use and patient satisfaction in conscious sedation nursing practices: a retrospective study. (2nd October 2021) - Parone, Linda; Rawal, Sahil; Ellis, Allison; Peterson, Bryant; Escalante, Lourdes; Sharma, Ravi; Pandya, Bhavi; Kumar, Arnav; Panchal, Hemang B; Prakash, Meghanaprakash Hiriyur; Yadav, Ritu; Kanwar, Nidhi; et al.
Abstract : Background: Moderate sedation is performed frequently in the hospital setting for same-day, invasive procedures. The primary administrators of moderate sedation are nurses who have been trained to administer medication based on patient responsiveness, airway, ventilation and cardiovascular function. This study evaluated the safety and efficacy of nurse-administered conscious sedation by assessing medication use, clinical outcomes and patient satisfaction. Methods: Data from same-day, elective procedures in the cardiac catheterisation laboratory and interventional radiology departments were collected, including comorbidities, procedural characteristics and post-sedation questionnaires. Results: Procedure duration was found to be longer in the cardiac catheterisation laboratory (55 minutes; interquartile range: 37–81 minutes) than in interventional radiology (24 minutes; interquartile range 16–45 minutes; P value of <0.001). Associated comorbidities in the cardiac catheterisation laboratory compared to interventional radiology included hypertension in 103 patients (78% vs 44.7%, P =<0.001), heart failure in 23 patients (17.4% vs 3.2%, P =<0.001), arrhythmias in 20 patients (15.2% vs 1%, P =0.1), and chronic kidney disease in 44 patients (33.3% vs 14.9%, P =0.002). Conclusions: Patients receiving conscious sedation while undergoing procedures in the cardiac catheterisation laboratory and interventional radiology were found to have no adverse clinical outcomes, as evidenced by the absence of reversal agents and advanced airway requirements. The procedural duration of the catheterisation procedures were significantly longer than interventional radiology and patients received overall less sedation medication.